FACTORS PREDICTING THE LIKELIHOOD OF NON-SENTINEL LYMPH NODE METASTASES IN BREAST CANCER PATIENTS WITH A POSITIVE SENTINEL LYMPH NODE: A SINGLE-CENTER STUDY - Kondov, Borislav; Stojanovski, Sinisha; Bogdanova, Magdalena; Gruev, Viktor; Cholancheski, Risto; Atanasova, Ljubica; Kondov, Goran (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
This study aims to determine and appraise the factors predicting the likelihood of non-sentinel lymph node metastases in breast cancer patients, in order to avoid unnecessary axillary lymphadenectomy. A consecutive cohort study ascertained 133 patients with a detected sentinel lymph node, who met the inclusion criteria: early breast cancer (in T1, 2; N0 and M0 stage), tumor size of 5 cm or less and clinically negative axillary status. The patients were then divided into three groups, according to the SLN and NSLN status (group 1 = SLN -; group 2 = SLN +, NSLN -; group 3 = SLN +; NSLN +). Number of patients was n=98; n=19 and n=16, respectively. Aim of the study is to determine factors that can predict positivity of non-sentinel lymph nodes in condition when sentinel lymph nodes were positive. According to the correlation matrix, Kolmogorov-Smirnov test, when comparing the negative and positive NSLNs in the group of positive SLNs, whether NSLN will be positive or not, depends on the tumor size, number of detected NSLNs and pT. It also depends on the age, number of positive and negative SLNs, number of negative NSLNs, pN, G, stage, positivity of p53 and positivity of Her 2 new. Longer follow-up studies of a larger group of patients are required to define the exact factors contributing to a positive NSLN when SLN is positive. In our study the determined risk factors which contribute to the positivity of NSLNs were: age, number of identified and negative NSLNs, number of negative and positive SLNs, pN, G, stage of the disease,  positivity of p53 and positivity of Her 2 new. Keywords: lymphadenectomy, sentinel lymph node, non-sentinel lymph node, breast cancer, metastases, risk factors for positivity of SLND or NSLD.     https://doi.org/10.55302/JMS2251085k